Is Academic Procrastination Still a Problem among Junior High School? The Investigation of Academic Self-Efficacy and Parental Support as Predictor - Hifsy, Ifrah; Marjohan, Marjohan (Universitas Ahmad Dahlan, 2023)
This research is motivated by the still high incidence of academic procrastination among junior high school students. The purpose of this research is to examine whether academic self-efficacy and parental support contribute to students' academic procrastination. This research used a cross-sectional design, with a sample of 250 students selected through proportional stratified random sampling. The research instruments used included measurements of academic self-efficacy, parental support, and academic procrastination. Data were analyzed using multiple regression with the help of SPSS version 25.00. Research findings show that academic self-efficacy contributes negatively to academic procrastination (standardized beta = -.613, sig = .000), and parental support also shows a significant contribution (standardized beta = -.215, sig = .000). The implications of this research highlight the need to increase students' self-efficacy and parental support through a series of psychological interventions to reduce cases of academic procrastination among students.